Blood Periipin A Levels in Apparently Healthy Obese and Non-Obese Adults in Accra. - Letsu, B.S. (University Of Ghana, 2017)
Perilipins are regulatory proteins that cover the surfaces of lipid droplets located in adipocytes. They protect against basal lipolytic activity of hormone sensitive lipase and promote its catalytic activity during stimulated lipolysis. Perilipin A is the commonest form found on the surface of lipid droplets in adipocytes and may be affected by obesity. With increasing adipocyte size in obesity, the expression of perilipin protein and its regulatory role in lipolysis may be lowered which may increase the release of free fatty acids leading to insulin insensitivity. The aim of this study was to assess blood Perilipin A levels in apparently healthy obese and non-obese subjects and relate it to percentage body fat, insulin resistance and blood lipid levels. A study population consisted of 46 apparently healthy obese and 40 non-obese subjects. The subjects recruited for the study were from a number of Ga communities located along the coast within the Ablekuma South Sub-metro who provided details on their health status through a questionnaire. Anthropometrics, fasting lipids and glucose were measured at baseline. Baseline fasting glucose values were used to confirm non-diabetic status of subjects. Serum perilipin A and insulin were measured on fasting samples using commercially available ELISA assays following strictly the manufacturer’s protocol. The HOMA2 calculator was used to calculate insulin sensitivity. Blood perilipin A (ng/L) level was significantly higher in the non-obese compared with obese subjects (159.9±32.6 vs 130.8±23.9, p<0.0001). Blood perilipin A levels were higher in obese males than obese females (135.1±29.3 vs 126.4±19.5, p=0.218). Glucose and insulin levels were not significantly higher in obese than non-obese subjects (5.9±0.5 vs 4.9±0.5) and (11.8±3.8 vs 11.1±3.3) respectively. HOMA-IR level was higher in the obese compared with non-obese subjects (1.47± 0.5 vs 1.40±0.4, p=0.480). BMI (40.5±5.9 vs 22.9±2.6, p<0.0001), visceral fat (18.2±5.8 vs 5.9±2.6, p<0.001) and percentage body fat (44.1±10.1 vs 25.5±9.5, p<0.001) were about two fold higher in the obese compared with non-obese subjects. Except for HDL all other lipid parameters were significantly higher in the obese than non-obese subjects (p<0.05 in all cases). There was no significant correlation between perilipin A levels and age (p=0.87), BMI (p=0.91), visceral fat (p=0.10) and % body fat (p=0.162). However, perilipin A generally showed a negative relationship with these parameters except for visceral fat. There was no significant correlation between perilipin A levels and HOMA-IR (p=0.23). Perilipin A levels were not significantly correlated with all lipid parameters (p>0.05 in all cases). Except for T.CHOL/ HDL ratio that showed a positive relationship, all other lipid parameters showed a negative relationship with perilipin A levels. HOMA-IR showed no significant correlation with age (p=0.07), BMI (p=0.963) and % body fat (p=0.69) but showed a significant correlation with visceral fat (p=0.049). There was significant positive correlation between HOMA-IR and insulin levels (p<0.001) but no significant correlation between HOMA-IR and all lipid parameters (p>0.05 in all cases). In conclusion, blood perilipin A levels were significantly higher in the non-obese subjects compared to the obese which may have accounted for the lower lipid levels but showed no significant correlations with HOMA-IR and serum lipid levels.
Thesis (MPhil.)
Keywords: Blood Periipin; Obese; Basal Lipolytic Activity; Catalytic Activity; Ghana